2018
DOI: 10.1002/2018gl077209
|View full text |Cite
|
Sign up to set email alerts
|

Improved Teleconnection‐Based Dynamical Seasonal Predictions of Boreal Winter

Abstract: Climate and weather variability in the North Atlantic region is determined largely by the North Atlantic Oscillation (NAO). The potential for skillful seasonal forecasts of the winter NAO using an ensemble‐based dynamical prediction system has only recently been demonstrated. Here we show that the winter predictability can be significantly improved by refining a dynamical ensemble through subsampling. We enhance prediction skill of surface temperature, precipitation, and sea level pressure over essential parts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
113
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 66 publications
(126 citation statements)
references
References 47 publications
3
113
0
1
Order By: Relevance
“…Seasonal (DJF) means of sea-level pressure (SLP) were used from the region limited to 20 • N and 90 • N latitudes and 90 • W and 60 • E longitudes. In this study, we use the ERA-Interim NAO as a reference, and the ensemble-based seasonal prediction of NAO from Dobrynin et al (2018), normalized by their respective standard deviations. In this study, we use the ERA-Interim NAO as a reference, and the ensemble-based seasonal prediction of NAO from Dobrynin et al (2018), normalized by their respective standard deviations.…”
Section: Nao Index and Subsamplingmentioning
confidence: 99%
See 4 more Smart Citations
“…Seasonal (DJF) means of sea-level pressure (SLP) were used from the region limited to 20 • N and 90 • N latitudes and 90 • W and 60 • E longitudes. In this study, we use the ERA-Interim NAO as a reference, and the ensemble-based seasonal prediction of NAO from Dobrynin et al (2018), normalized by their respective standard deviations. In this study, we use the ERA-Interim NAO as a reference, and the ensemble-based seasonal prediction of NAO from Dobrynin et al (2018), normalized by their respective standard deviations.…”
Section: Nao Index and Subsamplingmentioning
confidence: 99%
“…The EOF-based NAO index is represented by the principal component of the leading EOF of SLP (Kutzbach, 1970). Dobrynin et al (2018) reported a subsampling method, which considers well-established NAO teleconnection such as links between the October sea surface temperature in the North Atlantic, snow depth in Eurasia, the stratospheric air temperature in the Northern Hemisphere, September sea ice volume in the Arctic, and the subsequent winter NAO. We define years of strongly positive NAO + and negative NAO − phases as years with anomalies of the NAO that exceed the mean NAO value by ±1 standard deviation.…”
Section: Nao Index and Subsamplingmentioning
confidence: 99%
See 3 more Smart Citations